An examination of the validity of neuropsychological and physical testing batteries in Latin-American adults aged over 55 years - Hernández Gamboa, Rebeca (2023)
Background. Valid and reliable measurements are necessary to understand and monitor age-related changes. Aims To describe the factor structure and provide validity evidence of a neuropsychological and a physical testing batteries using factor analysis. Methods. We performed a secondary analysis of data from the Epidemiology and Development of Alzheimer’s Disease (EDAD) project. Community-dwelling adults aged 55 to 85 years underwent comprehensive physical and neuropsychological assessments. An exploratory factor analysis was performed on both assessment batteries. The models were later confrmed with a random subsample using confrmatory factor analysis. Results. Data from 238 adults (163 females and 75 males) was included. The neuropsychological model revealed a fourfactor structure formed by “Executive Functioning”, “Verbal Memory”, “Logical Memory”, and “Labeling And Reading” (Extraction Sums of Squared Loadings [ESSL]=56.41% explained variance; Standardized Root Mean Square Residual [SRMSR]=0.06; Comparative Fit Index [CFI]=0.98). The physical model was formed by a two-factor structure including “Health-related Fitness and “Functional Fitness” (ESSL=50.54% explained variance; SRMSR=0.07; CFI=0.93). Discussion. To our knowledge, this is the frst study to analyze the structure of comprehensive testing batteries for the Latin-American older adults. Our analysis contributes to the understanding of theoretical constructs that are evaluated in the EDAD project. Conclusion. Our fndings provide validity evidence for simplifed and reduced testing batteries, which imply shorter testing times and fewer resources.